Relativism, Contextualism, and Temporal Perspective - Colomina-Almiñana, Juan (Daimon Revista Internacional de Filosofia, 2018)
This article argues that there is no such thing as a proposition with variable truth-values, at least when considering English tensed sentences. This means that any account of meaning and truth that appeals to a notion of proposition with different truth-values at different times is necessarily at fault. The reason is that any evaluation context is always dominated by a temporal perspective beyond both speaker and audience and embedded to the communicational common ground. Only an approach that takes this into consideration is successful.